Success rate and complications of endonasal dacryocystorhinostomy with unciformectomy - Yang, Jae Wook (Springer-Verlag, 2012)
BACKGROUND: Endonasal dacryocystorhinostomy (DCR) has been widely used to treat nasolacrimal duct obstruction. Here, we evaluated the anatomical advantages of the uncinate process as a landmark and to study the effect of unciformectomy on success rate and complications of endonasal DCR . METHODS: In total, 288 eyes of 265 adult patients who underwent endonasal DCR between January 2003 and February 2010 were reviewed retrospectively. The eyes were classified into two groups, according to whether unciformectomy was performed or not. All surgical procedures and surgical indications were the same except unciformectomy and endonasal DCR was performed by one surgeon. Unciformectomy was performed by resecting the anterior part of uncinate process. RESULTS: One hundred and eighty-six eyes of 168 patients received endonasal DCR with unciformectomy, and 102 eyes of 97 patients received endonasal DCR alone. The average success rate of endonasal DCR with unciformectomy was 97.8 % and that of endonasal DCR alone was 90.2 %, with statistically significant difference (Student's t-test, p-value < 0.05). There were 14 eyes with post-operative nasolacrimal obstruction, caused by granuloma in five eyes, intranasal synechia in two eyes, membranous obstruction in six eyes, and canalicular stenosis in one eye. There were no serious complications such as orbital fat prolapse, cerebrospinal fluid leak, or delayed hemorrhage. CONCLUSIONS: Anterior resection of the uncinate process gives improved access to the lacrimal bone by exposing the medial aspect of the lacrimal fossa and forming the precise location of the osteotomy on the lacrimal bone during endonasal DCR. Thus, the uncinate process can be used as an anatomical landmark for endonasal DCR. The unciformian endonasal DCR improves operation success rate by allowing access to the large space of the nasal cavity and reducing the synechiae of the nasal cavity.